The Clinicopathological Significance and Prognostic Value of Androgen Receptor in Endometrial Carcinoma: A Meta-Analysis - Wu, Xirong; Zhong, Xiuli; Huo, Xiaoqing; Zhang, Junrong; Yang, Xiaoqing; Zhang, Yuquan (Frontiers in Oncology, 2022)
Background The role of androgen receptor (AR) in evaluating the prognosis of patients with endometrial cancer (EC) remains controversial. Here, we performed a meta-analysis to assess whether AR expression improves EC survival outcomes. Methods We searched related articles published before August 2021 in PubMed, EMBASE, and Web of Science. The association between AR expression and patient prognosis was estimated with hazard ratios (HRs) and odds ratios (ORs) with their corresponding 95% confidence intervals (95% CIs). The review is registered on PROSPERO, registration number: CRD42021268591. Results Ten studies including 1,485 patients were enrolled in the meta-analysis. The results showed that AR expression in EC tissues was associated with a better survival in crude analyses (HR = 1.63, 95% CI = 1.32–2.02, P < 0.001). However, no significant relation was found after the adjustment of the confounding factors (HR = 1.68, 95% CI = 0.75–3.75, P = 0.205). In subgroup analyses, grade 1–2 disease, stage I–II disease, negative lymph node status, and lack of the lymphovascular invasion were more common in AR-positive groups (OR = 0.47, 0.48, 0.37, and 0.57; 95% CI = 0.45–0.62, 0.35–0.65, 0.24–0.56, and 0.37–0.89). Furthermore, AR expression was more common in endometrioid cancers (OR = 2.39, 95% CI = 1.79–3.20). Conclusions AR expression is significantly associated favorable characteristics including low-grade disease, early-stage disease, negative lymph node status, and lack of the lymphovascular invasion and a specific histology—endometrioid cancer. However, AR is not an independent prognostic factor.